The Effects of Inflammation on Alpha 1 Antitrypsin Levels in a National Screening Cohort - Sanders, Christopher L.; Ponte, Amy; Kueppers, Friedrich (Chronic obstructive pulmonary disease, 2018)
Alpha 1 Antitrypsin (AAT) is a highly polymorphic serum protein. Several genetic variants are associated with varying degrees of decreased serum levels; however, these levels can rise in response to infection, inflammation, injury and estrogen levels. Although the effect of inflammation is well established, it has never been studied quantitatively with respect to specific genotypes in a large representative sample. Using data from a national AAT deficiency-targeted screening cohort, we evaluated AAT levels of patients with normal and deficiency genotypes in response to inflammation, indicated by elevated serum C-reactive protein (CRP). Additionally, we utilized a regression analysis to adjust for the effect of inflammation for each genotype. Across all stratified genotype groups, increased AAT levels were observed in patients with CRP ≥5 mg/L. Different AAT phenotypes reacted differently in the acute phase; M showed a strong response and Z a reduced reaction. Nevertheless, we discovered that inflammation significantly masked clinically relevant base AAT levels in some PI * MZ individuals; approximately a quarter of PI * MZ samples showed signs of inflammation. Median AAT levels (mg/dL) in the presence of inflammation are given for several genotypes; numbers in parentheses are levels from the cohort without inflammation/adjusted levels from the cohort with inflammation using the newly devised algorithm: PI * MM: 162 (142/140); PI * MS: 136 (117/115); PI * MZ: 104 (85/89); PI * MF: 161 (132/141); PI * SS: 115 (96/91); PI * SZ: 66 (54/50). We conclude that simultaneous determinations of CRP and AAT levels, and genotyping are clinically valuable in defining AAT variants and that the effect of inflammation can be adjusted for.